Strategi pengembangan potensi Situ Cileunca sebagai destinasi wisata di Pangalengan - Sidqiyah, Chamiyatus; Hardi, Ahmad Rustama; Kurniadewi, Elisa; Putri, Sifana Nur Amelia; Ratunadhani, Agiva; Pradhifa, Aranaila Cayenne (Universitas Negeri Malang, 2025)
Strategy for developing the potential of Situ Cileunca as a tourism destination in Pangalengan This research aims to identify the tourism potential in Warnasari Village, Pangalengan District, and to formulate effective development strategies to establish Situ Cileunca as a premier tourist destination. The research approach employs a descriptive qualitative using Participatory Rural Appraisal (PRA), field observations, interviews, and document studies. SWOT analysis (strengths, weaknesses, opportunities, threats) is used to formulate strategies for developing Situ Cileunca as a tourist destination. The results indicate that Situ Cileunca possesses attractive natural and cultural potential, supported by strong community engagement. However, challenges remain in infrastructure, lack of promotional strategies, and tourism management. Based on these findings, this research proposes development strategies for Situ Cileunca as a tourist destination, including: (1) improvement of tourism infrastructure and facilities, (2) development of nature and culture-based tourist attractions, (3) empowerment of local communities in tourism management, (4) strengthening partnerships between the government, private sector, and communities, and (5) enhancement of tourism promotion through digital media. Penelitian ini bertujuan untuk mengidentifikasi potensi wisata di Desa Warnasari, Kecamatan Pangalengan, serta merumuskan strategi pengembangan yang efektif untuk menjadikan Situ Cileunca sebagai destinasi wisata unggulan. Metode yang digunakan pada penelitian ini adalah kualitatif deskriptif dengan teknik PRA (Participatory Rural Appraisal), observasi lapangan, wawancara, dan studi dokumentasi. Analisis SWOT (kekuatan, kelemahan, peluang, ancaman) digunakan untuk merumuskan strategi pengembangan Situ Cileunca sebagai destinasi wisata. Hasil penelitian menunjukkan bahwa Situ Cileunca memiliki potensi alam dan budaya yang menarik serta dukungan masyarakat, tetapi masih menghadapi tantangan dalam segi infrastruktur, strategi promosi, serta pengelolaan manajemen sektor wisata. Berdasarkan temuan tersebut, penelitian ini mengusulkan strategi pengembangan Situ Cileunca sebagai destinasi wisata meliputi: (1) peningkatan infrastruktur dan fasilitas wisata, (2) pengembangan atraksi wisata berbasis alam dan budaya, (3) pemberdayaan masyarakat lokal dalam pengelolaan wisata, (4) penguatan kemitraan antara pemerintah, swasta, dan masyarakat, serta (5) peningkatan promosi wisata melalui media digital.